Persepsi Petani terhadap Kualitas Layanan Penyuluh Pertanian Lapangan (Kasus di Subak Durentaluh, Desa Belimbing, Kecamatan Pupuan, Kabupaten Tabanan) - I PUTU PRATYA PERMANA; I WAYAN SUDARTA; I KETUT SURYA DIARTA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2016)
Abstract Farmers Perception on the Quality of Field Agricultural Extension Services (A Case in Subak of Durentaluh, Belimbing Village, Pupuan Sub-district, Tabanan Regency) Extension services can be a means of effective policies to promote agricultural development in a situation where farmers are not able to achieve their goals. Extension activities in agricultural development act as a bridge that connects between the practice run by farmers and their knowledge and technology that are always evolving. The purpose of this study was to analyze the farmers' perceptions of the service quality of the PPL and to analyze the obstacles encountered by the PPL in carrying out their duties in Subak of Durentaluh, Belimbing Village, Pupuan Sub-district, Tabanan Regency. This study used qualitative descriptive analysis. The results showed that the level of farmers' perceptions of the service quality of PPL in Subak of Durentaluh in Belimbing Village was of good category, by achieving an average score of 4.15 (82.90% of the maximum score).The constraints faced the PPL in implementing the basic tasks were most dominantly concerned with technical aspects. Extension tools owned are extremely minimal, only using white board, markers, and print out materials. It is expected that the PPL is able and selective to encourage farmers to apply appropriate innovations in order to prove the recommended innovation successful if applied. It is necessary to have attention from the government to provide the availability of supporting facilities to make the extension services more optimal.